Calreticulin Immunohistochemistry in Myeloproliferative Neoplasms - Evolution of a New Cost-Effective Diagnostic Tool: A Retrospective Study with Histological and Molecular Correlation - Sanjeet ROY; Marie Therese MANIPADAM; Poonkuzhali BALASUBRAMANIAN (Federation of Turkish Pathology Societies, 2022)
Objective: Recent WHO 2017 guidelines mandates mutational analysis for the diagnosis of myeloproliferative disorders (MPN). JAK2V617F has been found in only 50-60% of Primary myelofibrosis (PMF) and Essential thrombocythaemia (ET). A recently discovered somatic Calreticulin (CALR) mutation has been linked to MPN. This mutation leads to a common 36 amino acid C-terminus that can be detected accurately by immunohistochemistry (IHC). Limited published literature exists on the utility of CAL2IHC as a diagnostic tool. The study aimed to validate the sensitivity and specificity of CAL2IHC for its use as a cost effective and rapid diagnostic tool. Material and Method: Subjects included 23 patients of MPN (15 PMF, 6 ET, 2 PV (Polycythaemia Vera)), diagnosed between January 2014 to November 2016 with adequate available tissue for histopathological and mutational analysis. Mutational analysis had been performed with Bidirectional Sanger sequencing. CAL2IHC was performed in all cases and the sensitivity and specificity of CAL2 IHC to identify the Calreticulin mutation was evaluated with respect to comparison with the gold standard mutation analysis. Results: In the 23 MPN patients, CAL2 IHC detected CALR mutation with a sensitivity of 95% and a specificity of 100%. Both cases of PV were negative for CAL2IHC. CAL2IHC showed cytoplasmic positivity in ET (2-3+) and PMF (1-3+) with (62-69%) positive megakaryocyte staining. All 6 ET cases and all 14/15 PMF cases were CAL2IHC positive, and these results were concordant with CALR mutational analysis. Conclusion: Anti-CAL2 immunohistochemistry is a specific and a sensitive marker to detect CALR mutation. Its' cost effectiveness and fast results are quite advantageous as compared to molecular analysis.